IMPACT OF MOTIVATIONAL FACTORS ON ORGANIZATIONAL COMMITMENT OF BANK EMPLOYEES - Lekić, Nemanja; Vukosavljević, Dejan; Vapa Tankosić, Jelena; Lekić, Snežana; Mandić, Slavica (Ekonomija - teorija i praksa, 2022)
Human resources are the most important potential of any organization, and therefore orgasnizations must find, attract and retain employees with appropriate knowledge and skills. This includes an adequate way of motivating and rewarding employees, which has a positive effect on their satisfaction, loyalty and commitment to the organization. The subject of the research are the parameters of employee motivation and organizational commitment in commercial banks. The research was conducted in 2019 on the territory of the Republic of Serbia on a sample of 667 respondents. Statistical data processing were be performed using the SPSS program. The aim of the paper is to analyze the interdependence of demographic factors and motivational factors of employees: amount of salary, cooperation and good relations with superiors, greater autonomy in the execution of work tasks and the decision-making process, better information on issues related to the future of the company, opportunities for advancement and additional education and job content. Also, with binary regression we determine the influence of motivational factors on organizational commitment. This research paper will show the ways in which different motivational factors affect the organizational commitment of bank employees, which can be a parameter for bank management in formulating a business strategy that will ensure their efficiency and business success.